Types and formation mechanisms of diagenetic fractures in shale - Yue Zeng; Miao Shi; Jinchuan Zhang; Zhongming Li; Jialiang Niu; Tianshu Yuan; Yuchao Ma; Menglian Sun; Lixun Bai (Sedimentary Geology, 2026)

Towards low-carbon heavy oil recovery: multi-source renewable energy integration and multi-objective optimization - Qi Liu; Hongjuan Hou; Yaochen Wang; Min Deng; Tianshu Li; Yan Jia; Eric Hu (Fuel, 2026)

Corrigendum to “A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations” Aquaculture, Volume 612, Part 1, 15 January 2026, 743185 - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Collision-free path planning for underwater gliders in time-varying currents via dual-archive niching differential evolution - Zezhong Li; Rongshun Juan; Yang Li; Shoufu Liu; Tianshu Wang; Shuaikun Shi; Leihao Du; Wanjun Feng; Zhongke Gao (Ocean Engineering, 2026)

Mechanism of rice protein amyloid fibrils-induced structural changes of soybean protein during high-moisture extrusion: Focusing on multi-scale structural evolution - Jinming Ma; Kaizhi Li; Deyin Pan; Peng Wang; Mohamed E. Hassan; Wenyi Yang; Tianshu Zhang; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

A two-dimensional nanocatalytic engineered saliva immunosensor for acute myocardial infarction high-sensitivity detection - Jingyi Yang; Lei Li; Xuanyu Xiao; Yuting Zhong; Zetai Zheng; Yue Zhou; Tianshu Wang; Chenxu Wang; Wei Deng; Chenjun Xu; Chen Li; Qinsheng Hu; et al. (Chemical Engineering Journal, 2026)

How additives steer sewage sludge hydrochar properties: Divergent pathways of MgO/CaO versus sawdust in carbon/nutrient fate and magnetism - Chen Zhang; Guo Chen; Qinghai Wang; Huafen Li; Yanan Wan; Guoxin Sun; Ke Wang; Tianshu Chu; Ruilun Zheng (Bioresource Technology, 2026)

Reactive oxygen species in earthworm casts: a hidden driver of CO2 emissions and Fe‑associated organic carbon formation - Zheng Ni; Bin Jia; Tianshu Liu; Yuntao Yuan; Yanpei Li; Hanzhong Jia (Biology and Fertility of Soils, 2026)

Retraction notice to “Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China” [Sci. Total Environ. 898 (2023) 165303] - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A plasma metabolomics analysis reveals a panel of metabolic biomarkers for early pregnancy diagnosis in Hu sheep - Tianshu Dai; Wenqiao Li; Shengwei Pei; Tajmal Hussain Solangi; Xueying Zhang; Fadi Li; Xiangpeng Yue (Livestock Science, 2026)

Multi-omics identifies key genes regulating intramuscular metabolites to affect age- and gender-specific meat quality in sheep - Yali Song; Tianshu Dai; Shijie Tang; Zehu Yuan; Fadi Li; Weiwei Fu; Long Guo; Xueying Zhang; Xiangpeng Yue (Food Bioscience, 2026)

Experimental Investigation into the Effect of Process Parameters on Borehole Formation in Bedded Shale by Swirling Abrasive Water Jet - Kang Cheng; Zhongwei Huang; Jingru Hu; Jingbin Li; Bing Xi; Tianshu Wang; Huan Li; Gensheng Li (Rock Mechanics and Rock Engineering, 2026)

Curculigoside Alleviates CSDS-induced Depressive-like Behavior by Modulating Pyramidal Neuron Excitability and Synaptic Transmission - Yuhong Jing; Tianshu Zhang; Zihao Wei; Huaiyuan Wang; Tianqi Gao; Yanling Liu; Lin Cong; Lianbin Zhao; Shuoxin Xie; Lu Liu; Xinmeng Zhang; Tongrui Wu; et al. (NeuroMolecular Medicine, 2026)

Ammonium may emerge as the primary driver of future aerosol acidity, replacing the historical role of sulfate over the coastal area of North China: Insights from a megacity (Qingdao) - Wenshuai Li; Yaoyu Song; Tianshu Chen; Yuxuan Qi; Guanru Wu; Xinshuo Wang; Wenwen Xie; Lifang Sheng; Wencai Wang; Wenjun Qu; Yang Zhou (Atmospheric Environment, 2026)

Toward sustainable lithium recovery from brine: a hydrothermal carbon-coating strategy for minimizing Mn dissolution in ion-sieve adsorbents - Tianshu Bao; Congcong Li; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Lili Yu; Xinjuan Hou; Aiping Peng; Ming Ye (Resources, Conservation and Recycling, 2026)

Winter fallow straw–nitrogen co-application enhances rice yield and stability by regulating soil organic matter physical fractions and chemical composition - Xi Chen; Danni Li; Min Peng; Yueling Zhang; Tianshu Wang; Jingdong Mao; Shuihong Yao; Bin Zhang (Agriculture, Ecosystems & Environment, 2026)

Study on the erosion mechanism of calcium-based sand erosion-resistant materials in an ion-stress coupled environment - Tianshu Wang; Peng Li; Feiyu Yang; Kai Yi (Marine Georesources & Geotechnology, 2026)

Reinforcement learning-based path planning for underwater gliders using ocean current forecasts - Yatao Zhou; Yang Li; Rongshun Juan; Tianshu Wang; Zezhong Li; Shoufu Liu; Wei Ma; Zhongke Gao (Ocean Engineering, 2026)

Enhanced caproic acid production through electro-fermentation: A novel approach for resource utilization of lignocellulosic waste - Tianshu Liu; Jianzheng Li; Furao Wang; Jia Meng (Environmental Research, 2026)

Toward smart aquaculture: A review of multimodal methods, datasets, and applications from the modality perspective - Qinyue Zhang; Shasha Wang; Tianshu Zhang; Guiming Ren; Lingling Zhang; Yangfan Wang; Bing Zheng; Juan Li; Haiyong Zheng (Computers and Electronics in Agriculture, 2026)

A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Event-triggered model predictive control for trajectory tracking of underwater gliders in currents - Tianshu Wang; Rongshun Juan; Man Luo; Jin Chen; Yang Li; Yatao Zhou; Zhongke Gao (Ocean Engineering, 2026)

Change of chemical compositions of the regional free troposphere in North China during COVID-19: Observational evidence from the Mt. Tai observatory - Yue Sun; Yujiao Zhu; Can Dong; Yingnan Zhang; Yujian Bi; Di Wu; Xiangkun Yin; Hengqing Shen; Tianshu Chen; Hongyong Li; Yuqiang Zhang; Qinyi Li; et al. (Atmospheric Environment, 2026)

Ancient DNA sheds light on the mating strategies and genetic identity of Han nobles during the Northern and Southern Dynasties - Youyang Qu; Zhanrui Zhao; Chao Ning; Jiashuo Zhang; Tianshu Li; Dawei Cai; Dongyue Zhao (Archaeological and Anthropological Sciences, 2026)

Long-range straight-line path tracking for underwater gliders using reinforcement learning and ocean current forecasts - Yatao Zhou; Rongshun Juan; Yang Li; Tianshu Wang; Wei Guo; Ming Yang; Zhongke Gao (Ocean Engineering, 2025)

AI misuse of retracted literature: A comparative study of ChatGPT4o, deepseek, and grok 3 in stem cell research - Lan Yao; Tianshu Gu; Xuexin Li; Yan Jiao; Minghui Li; J. Carolyn Graff; Yulan Li; Weikuan Gu (The Science of Nature, 2025)
DeepSeek and Grok 3 appear as strong competitors to AI models, particularly the widely accepted model, ChatGPT. The accuracy of the utilization of data in retracted scientific articles has proven to be a significant challenge for AI as an assistant in scientific research. It is critical to understand whether and how three AI models handle information from retracted articles when they answer scientific questions. We collected retracted articles and used AI models to generate questions and analyzed the answers. The answers were compared and evaluated among three AI models. Here we show that these three models utilized 84 out of 93 retracted articles in their answers about stem cells. ChatGPT4o retrieved 74 out of 93 (80%) articles and recognized the retract status for 46 (62%) of them. DeepSeek only found one retracted article and did not realize its retraction status. Grok 4 retrieved 69 (74%) articles and recognized the retraction status of 46 (67%) of them. In cases when the retracted articles were not identified, ChatGPT fabricated articles 5 times out of 19 (26%) for its answers. Grok 3 fabricated 15 articles out of 24 (63%) for its answers. In 82 times of 93 (88%) answers, DeepSeek fabricated the articles in various forms. The answering styles from ChatGPT4o, DeepSeek, and Grok 3 are characterized by accurate and straightforward, a tangential structure and guesswork, and comprehensive and detailed answers, respectively. Analysis with non-retracted articles revealed the similar patterns of these models. This study suggests that, while no model is perfect, DeepSeek performed the worst when facing in-depth scientific real-world challenges. Much improvement has to be made before any of these AI models become problem-free and valuable for scientists.

Syringaldehyde Ameliorates Cognitive Dysfunction in APP/PS1 Mice by Stabilizing the NLRP3 Pathway - Ruidan Chen; Hua Gao; Tianshu Zhu; Ni Zheng; Yan Jin; Ming Li; Zhiming Lu (Molecular Neurobiology, 2025)

Understanding clouds and precipitation over the Mount Qomolangma: how does the aerosol activation effect exist? - Xiangde Xu; Wenyue Cai; Tianliang Zhao; Hua Zhang; Xueliang Guo; Wenqing Liu; Tianshu Zhang; Runze Zhao; Chong Wu; Yueqing Li; Lei Wang; Peng Yan; et al. (Science Bulletin, 2025)

Is destabilized coupled flat plate membrane technology valuable for high-salinity mine water treatment? - Liyao Wang; Xianfeng Tan; Jianguo Fan; Hongnian Chen; Tianshu Xu; Mengqing Li; Jinglan Hong (Environmental Research, 2025)

Naringenin targets and inhibits Monoamine Oxidase A/B to bidirectionally regulate intestinal motility. - Qi Li; Yi Chen; Yige Zhang; Canwei Xu; Ting Tang; Yunzhi Qian; Ong Shun seng; Yujuan Wang; Ling Fang; Tianshu Xu (Chemico-Biological Interactions, 2025)

Study on the propagation processes and driving mechanisms of meteorological, hydrological, and agricultural droughts on the Mongolian Plateau - Li Mei; Han Aru; Siqin Tong; Yongfang Wang; Enliang Guo; Tianshu Zhang; Shan Yin; Yuhai Bao (Journal of Hydrology, 2025)

Self-activated antibacterial mask through respiratory induced deformation and temperature variation - Liqi Wei; Li Liu; Qin Zhang; Wenye Xie; Zhiqi Yang; Xin Liu; Yunan Yang; Yining Chen; Yiping Ren; Tianshu Zou; Biao Zhang; Hongxia Ma; et al. (Chemical Engineering Journal, 2025)

Vertical distribution and regional transport of air pollution over Northeast China: Insights from an intensive aircraft study - Ye Shan; Yujiao Zhu; Haoxin Sui; Na Zhao; Hongyong Li; Liang Wen; Tianshu Chen; Yanbin Qi; Wenlong Qi; Xinfeng Wang; Yuqiang Zhang; Likun Xue; et al. (Atmospheric Environment, 2025)

Breeding for yield improvements increases soybean seed N uptake due to enhanced N fixation under soil compaction - Tianshu Wang; Li Wang; Huajun Sun; Shuihong Yao; Yili Meng; Dawei Guan; Xinhua Peng; Bin Zhang (Plant and Soil, 2025)

Codon Usage Pattern of Papillomavirus E6, E7, and L1 Genes Across Hosts - Xudong Liu; Kexin Li; Xiaojing Chen; Yaqian Li; Tianshu Sun; Roujie Huang; Yanan Shi; Zilong He; Lei Li (Current Microbiology, 2025)

Amplified urban heat island effect in southern china’s old towns following atmospheric regulation policies - Junxiao Zou; Hans W. Chen; Haodong Li; Qiao Wang; Guoqiang Wang; Kun Jia; Ziyue Chen; Chuanfeng Zhao; Wenzhong Shi; Yinshan Yang; Yahui Tang; Jiayi Chen; et al. (Sustainable Cities and Society, 2025)

Mitigating bias induced by missing data in new-generation geostationary satellite monitoring of ground-level NO2 via machine learning - Naveed Ahmad; Changqing Lin; Tianshu Zhang; Zhiyuan Li; Jhoon Kim; Cui Guo (Environmental Pollution, 2025)

Mushroom residue extract-based media enhanced the enrichment and isolation of cellulose-degrading bacteria - Xiaoli Luo; Tianshu Wang; Yili Meng; Li Li; Shuihong Yao; Huawei Wu; Jun Li (Bioresource Technology Reports, 2025)

A visual balance calculation method for wemaps combining fuzzy clustering and multi-factor driving - Rongjuan Ma; Haowen Yan; Xiaomin Lu; Zhaoyang Hou; Xiaolong Wang; Pengbo Li; Tianshu Chu; Fukang Mao (Earth Science Informatics, 2025)

Giant lacustrine bioherms in the northeastern Qinghai-Tibet Plateau (western Qaidam Basin) during the Early–Middle Miocene: Carbonate fabrics, growth patterns, and environmental significance - Hui Xie; Fei Li; Xiang Li; Jiangong Wang; Chaojin Lu; Yuefeng Shen; Yalan Li; Zengjun Wang; Tianshu Zhang; Yangfan Li; Tao Wu; Ying Li (Sedimentary Geology, 2025)

Long-term properties of grout-soil composite eroded by seawater environment in submarine tunnel - Chengqian Wang; Peng Li; QingSong Zhang; Tianshu Wang (Tunnelling and Underground Space Technology, 2025)

Insight into ion-induced stability degradation in all-perovskite tandem photovoltaics: quantitative characterization and effective manipulation strategies - Yining Bao; Tianshu Ma; Yuqi Zhang; Luolei Shi; Linling Qin; Changlei Wang; Guoyang Cao; Xiaofeng Li; Zhenhai Yang (Science Bulletin, 2025)

A novel mechanism of kisspeptin regulating ovarian granulosa cell function via down-regulating let-7b to activate ERK/PI3K-Akt pathway in Tan sheep - Tianshu Dai; Shihao Wei; Xiaofeng Li; Di Yang; Linsen Gui; Hui Xiang; Yun Ma; Xingang Dan (Domestic Animal Endocrinology, 2025)

Tracing carbon-water pressures in the Belt and Road Initiative region from a "historical-future" perspective - Ziheng Li; Yijie Zhai; Tianzuo Zhang; Shuo Wang; Kang Wang; Changting Li; Tianshu Xu; Jinglan Hong (Resources, Conservation and Recycling, 2025)

Design, synthesis, and application of negative ion-ion sieve synergistic adsorbent based on cross-linked carrier - Tianshu Bao; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Yong Wang; Xinjuan Hou; Aiping Peng; Ming Ye (Desalination, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Combining High-Throughput Screening and Machine Learning to Predict the Formation of Both Binary and Ternary Amorphous Solid Dispersion Formulations for Early Drug Discovery and Development - Tianshu Lu; Yiyang Wu; Ping Xiong; Hao Zhong; Yang Ding; Haifeng Li; Defang Ouyang (Pharmaceutical Research, 2025)

circPRMT10 regulated by QKI hypermethylation attenuates lung tumorigenesis induced by tobacco carcinogen NNK - Xietian Xiao; Yadong Li; Tianshu Lin; Yufei Liu; Hengfa Zheng; Yanhu Liu; Zhikang Chen; Yihui Ling; Yiguo Jiang; Qiuhan Hua (Journal of Hazardous Materials, 2025)

Insights into the environmental–economic sustainability of rice production in China - Liyao Wang; Tianzuo Zhang; Xinying Zhou; Tianshu Xu; Changting Li; Ziheng Li; Shuo Wang; Mengqing Li; Jinglan Hong (Journal of Cleaner Production, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Computer-driven formulation development of Ginsenoside Rh2 ternary solid dispersion - Tianshu Lu; Tongchuan Wu; Hao Zhong; Xue Li; Yunsen Zhang; Hao Yue; Yulin Dai; Haifeng Li; Defang Ouyang (Drug Delivery and Translational Research, 2025)

Variation of biogenic VOC contribution to ozone formation with reduced anthropogenic precursor emissions: Coupling online observation and future scenario simulation - Yuhong Liu; Tianshu Chen; Zhaokun Ma; Qinyi Li; Yang Gao; Likun Xue; Wenxing Wang (Science of The Total Environment, 2025)

Incentivizing emission controls toward clean air and carbon neutrality in China: Perspectives from a risk-based approach for air quality management - Kimberly Tasha Jiayi Tang; Changqing Lin; Zhe Wang; Tianshu Zhang; Lu Li; Tze Wai Wong; Cui Guo (Science of The Total Environment, 2024)

The interaction between plasma polymetals and lifestyle on cognitive dysfunction in occupational aluminum exposed workers: A cross-sectional study in China - Tianshu Wang; Lingshan Xue; Chenyang Li; Dan Zhao; Jiaping Huan; Xiao Han; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu; Baolong Pan; Jinzhu Yin; et al. (NeuroToxicology, 2024)

Similarity of Chinese and Pakistani oral microbiome - Xiaofang Sun; Binghua Han; Qian Han; Qiaoling Yu; Sijie Wang; Jie Feng; Tianshu Feng; Xiaoshan Li; Shiheng Zhang; Huan Li (Antonie van Leeuwenhoek, 2024)

Internally-cooled atmospheric water harvesting enabling improved productivity - Yaohui Feng; Lurong Ge; Qian Li; Ruzhu Wang; Tianshu Ge (Water Research, 2024)

The influence of mudstone lithofacies sedimentation on the development of shale oil “sweet-spot intervals” within large down-warped lacustrine basins in China - Youliang Feng; Zhi Yang; Wenqi Jiang; Hong Zhang; Tianshu Zhang; Chang Liu; Pan Li; Jichang Zhu; Xiaoni Wang (Marine and Petroleum Geology, 2024)

Sustainability assessment for China's intensive dairy farming: Integrating environmental and economic perspectives - Tianshu Xu; Tianzuo Zhang; Ziyue Cheng; Ziheng Li; Shuo Wang; Xinying Zhou; Changting Li; Liyao Wang; Mengqing Li; Jinglan Hong (Sustainable Production and Consumption, 2024)

Unveiling 3-D evolution and mechanisms of ozone pollution in Changzhou, China: Insights from lidar observations and modelling - ZhiQiang Liu; Yan Xiang; Ying Pan; Tianshu Zhang; WenLong Xu; Li Li (Environmental Pollution, 2024)

Sensitivity of cloud microphysics to aerosol is highly associated with cloud water content: Implications for indirect radiative forcing - Yuan Wang; Hailing Jia; Ping Zhang; Fang Fang; Jiayi Li; Lei Zhu; Yang Wang; Tianshu Wang; Jiming Li (Atmospheric Research, 2024)

m6A methylation in myocardial tissue of septic mice analyzed using MeRIP/m6A-sequencing and RNA-sequencing - Xue Liang; Xiaotong Hu; Jiao Li; Boyang Zhang; Tianshu Gu; Hualing Wang; Mingzhong Zhang; Xiaodong Xia; Siyu Guan; Wenfeng Shangguan; Shuai Miao; Weiding Wang; et al. (Functional & Integrative Genomics, 2024)

A Perspective on Evaluating Life Stage Differences in Drug Dosages for Drug Labeling and Instructions - Tianshu Gu; Guiying Wang; Edwin J. C. van den Oord; Emanuel Goldman; Chengyuan Yang; Ning Xie; Lan Yao; Cong-Yi Wang; Monica Jablonski; Kunal Ray; Fengxia Liu; Wensen Pan; et al. (The AAPS Journal, 2024)

Interference of microplastics on autotrophic microbiome in paddy soils: Shifts in carbon fixation rate, structure, abundance, co-occurrence, and assembly process - Jiaohui Fang; Zihao Sheng; Jian Liu; Changchao Li; Tianshu Lyu; Zhenyang Wang; Honghai Zhang (Journal of Hazardous Materials, 2024)

Carbon–water–energy footprint impacts of dyed cotton fabric production in China - Changting Li; Tianzuo Zhang; Xinying Zhou; Ziyue Cheng; Tianshu Xu; Ziheng Li; Jinglan Hong (Journal of Cleaner Production, 2024)

Promoting sustainable potato production - Insights from an integrated life cycle environmental–economic assessment - Tianzuo Zhang; Changting Li; Shuo Wang; Ziyue Cheng; Ziheng Li; Tianshu Xu; Xinying Zhou; Wei Chen; Jinglan Hong (Agricultural Systems, 2024)

A quantitative analysis of causes for increasing ozone pollution in Shanghai during the 2022 lockdown and implications for control policy - Yingnan Zhang; Qingyan Fu; Tao Wang; Juntao Huo; Huxiong Cui; Jiangshan Mu; Yue Tan; Tianshu Chen; Hengqing Shen; Qinyi Li; Likun Xue (Atmospheric Environment, 2024)

An atmospheric water harvesting system based on the “Optimal Harvesting Window” design for worldwide water production - Qian Li; Zhao Shao; Qihong Zou; Quanwen Pan; Yao Zhao; Yaohui Feng; Wenwen Wang; Ruzhu Wang; Tianshu Ge (Science Bulletin, 2024)

Efficient caproic acid production from lignocellulosic biomass by bio-augmented mixed microorganisms - Tianshu Liu; Jianzheng Li; Xinyu Hao; Jia Meng (Bioresource Technology, 2024)

Coupling use of stable isotopes and functional genes as indicators for the impacts of artificial restoration on the carbon storage of a coastal wetland invaded by Spartina alterniflora, southeastern China - Tianshu Chu; Danyang Li; Yi-Jia Shih; Yuqing Guo; Kai Liu; Fenfen Ji; Jun Li; Yuzhu Yin; Ruohai Chen (Frontiers in Marine Science, 2024)
Coastal wetlands are characterized by high production and thus play an important role in global climate change. In past decades, the invasion of Spartina alterniflora has caused many problems of coastal wetlands in southeastern China, and the restoration of such areas was mainly conducted by replacing Spartina alterniflora with mangrove plants. This may impact the carbon storage dynamics in such areas. In this study, stable isotopes (δ 13 C and δ 15 N) and molecular analysis were used to reveal the impact of artificial restoration on the carbon storage of Quanzhou Bay Estuary Wetland Natural Reserve. The major results are as follows: (1) the change in dominant plants results in a changing major source of soil organic matter, from external sources to mangrove plants; (2) the decrease in soil organic matter following the removal of Spartina alterniflora may be primarily caused by the loss of external organic matter, while the production of mangroves may offset such loss and enhance the content and stability of carbon storage over the long term; (3) microbial CO 2 assimilation may serve as an alternative source of bioavailable carbon and thus support the activity of benthic community. Our results revealed the long-term benefits of such restoration on the carbon storage function of wetlands invaded by Spartina alterniflora . Furthermore, the integrating of isotopic tracers and molecular technology may provide new insights in understanding the response of the carbon storage in coastal areas to human activity.

Process intensification of tar chemical looping reforming based on ReaxFF reaction kinetics investigation - Zhe Li; Tianshu Wang; Yang Sun; Zhe Cui; Bin Liu; Wende Tian (Journal of Cleaner Production, 2024)

Concentrated fireworks display-induced changes in aerosol vertical characteristics and atmospheric pollutant emissions - Lingjian Duanmu; Weiwei Chen; Li Guo; Jing Fu; Bo You; Hongwu Yang; Tianshu Zhang (Atmospheric Environment, 2024)

Soil compaction development facilitated the decadal improvement of the root system architecture and rhizosheath soil traits of soybean in the North China Plain - Li Wang; Tianshu Wang; Shuihong Yao; Huajun Sun; Bin Zhang (Soil and Tillage Research, 2024)

Hazard or Non-Hazard Flood: Post Analysis for Paddy Rice, Wetland, and Other Potential Non-Hazard Flood Extraction from the VIIRS Flood Products - Donglian Sun; Tianshu Yang; Sanmei Li; Mitchell Goldberg; Satya Kalluri; Sean Helfrich; Bill Sjonberg; Lihang Zhou; Qingyuan Zhang; William Straka; Ruixin Yang; Fernando Miralles-Wilhelm (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Performance analysis of a rotary desiccant wheel using polymer material with high water uptake and low regeneration temperature - Yanan Xue; Qian Li; Ruzhu Wang; Tianshu Ge (International Journal of Refrigeration, 2024)

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

Research on autonomous decision-making technology for once-through steam generator - Ren Yu; Cheng Li; Wenmin Yu; Xiaosen Song; Tianshu Wang (Annals of Nuclear Energy, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

RETRACTED: Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2023)

Uncovering the energy-carbon-water footprint of waste rubber recycling: Integrated environmental and economic perspectives - Xinying Zhou; Yijie Zhai; Tianzuo Zhang; Ziheng Li; Ziyue Cheng; Changting Li; Tianshu Xu; Jinglan Hong (Journal of Environmental Management, 2023)

Changes of heavy metal concentrations in farmland soils affected by non-ferrous metal smelting in China: A meta-analysis - HaiXin Yang; RongRong Li; JiaSheng Li; YuRu Guo; TianShu Gao; DongGang Guo; QuanXi Zhang (Environmental Pollution, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Biogenic volatile organic compounds enhance ozone production and complicate control efforts: Insights from long-term observations in Hong Kong - Yingnan Zhang; Jianing Dai; Qinyi Li; Tianshu Chen; Jiangshan Mu; Guy Brasseur; Tao Wang; Likun Xue (Atmospheric Environment, 2023)

Life cycle environmental and cost assessment of prefabricated components manufacture - Ziyue Cheng; Tianzuo Zhang; Xinying Zhou; Ziheng Li; Yuke Jia; Ke Ren; Tianshu Xu; Changting Li; Jinglan Hong (Journal of Cleaner Production, 2023)

Horizontal ecological compensation mechanism and green low-carbon development in river basins: evidence from Xin’an River basin - Tianshu Quan; Hui Zhang; Jing Li; Binqiang Lu (Environmental Science and Pollution Research, 2023)

Corrigendum to “Chemical drivers of ozone change in extreme temperatures in eastern China” [Sci. Total Environ. 874 (2023) 162424] - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Chemical drivers of ozone change in extreme temperatures in eastern China - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

Insight into the dynamics of drinking water resistome in China - Mian Gul Hilal; Binghua Han; Qiaoling Yu; Tianshu Feng; Wanghong Su; Xiangkai Li; Huan Li (Environmental Pollution, 2023)

How can ecosystem status be more comprehensively reflected? A case study of Jinan City, China - Ziheng Li; Yijie Zhai; Tianzuo Zhang; Xinying Zhou; Ziyue Cheng; Tianshu Xu; Changting Li; Jinglan Hong (Science of The Total Environment, 2023)

Effect of chlorogenic acid on lipid metabolism in 3T3-L1 cells induced by oxidative stress - Libo Liu; Chenyi Zhang; Min Zhai; Tianshu Yu; Mengqi Pei; Peng Du; Aili Li; Jiayi Yan; Chun Li; Guofang Zhang (Food Bioscience, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

What are the Lacustrine Fine-Grained Gravity Flow Sedimentation Process and the Genetic Mechanism of Sweet Sections for Shale Oil? - Caineng Zou; Youliang Feng; Zhi Yang; Wenqi Jiang; Songqi Pan; Tianshu Zhang; Xiaoni Wang; Jichang Zhu; Jiarui Li (Journal of Earth Science, 2022)

Role of metformin in overweight and obese people without diabetes: a systematic review and network meta-analysis - Fuhai Hui; Yingshi Zhang; Tianshu Ren; Xiang Li; Mingyi Zhao; Qingchun Zhao (European Journal of Clinical Pharmacology, 2019)

Bioinformatic analysis of the complete genome sequence of Pectobacterium carotovorum subsp. brasiliense BZA12 and candidate effector screening - Yufei Huang; Changyuan Liu; Hui Wang; Tianshu Guan; Li Liu; Shuyi Yu (Journal of Plant Pathology, 2019)

Effect of Low-Selenium/High-Fat Diet on Pig Peripheral Blood Lymphocytes: Perspectives from Selenoproteins, Heat Shock Proteins, and Cytokines - Tianqi Liu; Tianshu Yang; Tingru Pan; Ci Liu; Shu Li (Biological Trace Element Research, 2018)

Isolation and characterization of twenty-one novel microsatellite loci for the black cicada, Cryptotympana atrata (Hemiptera: Cicadidae) - Wanchao Zhu; Haotian Li; Huanxin Zhang; Honghai Zhang; Tianshu Lv; Shuyu Xue; Jun Chen (Applied Entomology and Zoology, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Characterization of a cyanobacterial-like uptake [NiFe] hydrogenase: EPR and FTIR spectroscopic studies of the enzyme from Acidithiobacillus ferrooxidans - Olga Schröder; Boris Bleijlevens; Thyra E. de Jongh; Zhujun Chen; Tianshu Li; Jörg Fischer; Jochen Förster; Cornelius G. Friedrich; Kimberly A. Bagley; Simon P. J. Albracht; Wolfgang Lubitz (JBIC Journal of Biological Inorganic Chemistry, 2007)